The first picture archiving and communication system in Lao People's Democratic Republic: Changes in the utilization rate of imaging tests in the first year after implementation. (October 2016) - Hwang, In-Chang; Lee, Kil Won; Park, Sang Soon; Chanthanoulay, Siamphone; Sisavanh, Malouny; Rajpho, Virasack; Kim, Mijin; Billamay, Somxay; Phangmanixay, Sommanikhone; Oudavong, Bounleua
Highlights: The first PACS in Lao PDR was implemented at the Children's Hospital. Utilization rate of imaging test significantly increased after PACS implementation. Our results suggest a potential benefit of PACS for quality of care in Lao PDR. Benefits of PACS can be realized even in resource-limited settings. Abstract: Background: Implementation of the Picture Archiving and Communication System (PACS) is more challenging in developing countries than in developed countries. Given that the first PACS in Lao People's Democratic Republic (PDR) was successfully installed at the Children's Hospital of Lao PDR, we aimed to investigate whether the utilization rate of imaging tests increased after PACS implementation. Methods: PACS was implemented at the Children's Hospital of Lao PDR in December 2014. We compared the utilization rates of imaging tests including X-ray and ultrasound examinations between the pre-PACS period (from December 2013 to November 2014) and the post-PACS period (from December 2014 to November 2015). The utilization rate was defined as the number of imaging tests divided by the number of patients per month. Results: The average number of total imaging tests was 225.8/month (standard deviation [SD], 37.7) during the 1-year pre-PACS period and was 269.4/month (SD, 38.5) during the 1-year post-PACS period (P = 0.0103). The utilization rate of total imaging tests significantly increased after PACS implementation (pre-PACS, 2.47%/month; post-PACS, 4.23%/month; P < 0.0001). Increased utilization rates were observed for both X-rays (pre-PACS, 1.65%/month; post-PACS, 2.38%/month; P = 0.0004) and ultrasound examinations (pre-PACS, 0.82%/month; post-PACS, 1.85%/month; P = 0.0001). Conclusions: The implementation of PACS at the Children's Hospital of Lao PDR resulted in a significant increase in the utilization rate of imaging tests, suggesting the indirect benefit of improved quality of care. Our findings showed that the benefits of PACS can be realized even in a resource-limited country such as Lao PDR.